From Political Philosophy to Peace Architecture: Revitalizing Waqf within Islamic Political Thought for Community Security and Conflict Transformation - Ibrahim Isa Bello; Adamu Abubakar Muhammad; Abdullah A Afifi; Shaaban Idris Abdallah; Bilyaminu Yusuf; Murjanatu Yusuf (Perwakilan: Journal of Good Governance, Diplomacy, Customary Institutionalization and Social Networks, 2026)
In view of the chronic growth of conflicts, community insecurities, political instabilities, forced displacement, and socioeconomic inequalities in most Muslim societies, there has been a growing interest among academia and policymakers on the capabilities of indigenous governance institutions for sustainable peace and inclusive development. Despite the preponderance of state-centered approaches, liberal peace approaches, and humanitarian interventions in current peacebuilding agendas, much less attention has been paid to the constructive role of Islamic endowment (waqf) institutions as sustainable community security mechanisms and conflict resolution tools. Historically, waqf institution served not only as an institution for public charities but as one of the most robust institutions of Islamic political governance, which financially supports the implementation of policies aimed at developing education, health facilities, administration of justice, construction of public amenities, poverty alleviation, and social welfare thus contributing to social harmony and political stability. However, the waqf governance and conflict transformation functions remain understudied by the contemporary scholarship. This paper presents a conceptual framework that recontextualizes the role of waqf in the broader stream of Islamic political philosophy as an adaptive device in constructing lasting peace architecture. It employs a qualitative conceptual research design drawing from Islamic concepts of Siyasah Shar’iyyah, Maqasid al-Shariah, institution governance theory, and conflict transformation theory to explore this question based on a thorough review and synthesis of classical Islamic jurisprudence, modern scholarly works, and international policy documents. It finds out that Waqf has a great potential institutional capacity to address root causes of conflicts in a peaceful manner through equity-based wealth redistribution, social development, social protection, economic empowerment, mediation, and inclusive governance. The study presents a new model namely: Waqf Peace Architecture Framework (WPAF) that integratively links Islamic political philosophy and modern peace building strategy. It argues that reconstituting waqf as a governance institution rather than just as a charitable institution can foster community resilience, address social inequity, promote social trust and build up social capacity that transforms conflicts sustainably. The research ends with proposing recommendations for comprehensive policy reforms, institutional restructuring, and capacity development initiatives including institutional innovations and Waqf 2.0 in order to bring waqf institution into the current global peace architecture.